Do Russian Firms Need ISO Certification for Exporting? - Victoria Golikova; Boris Kuznetsov (European Regional Science Association (ERSA), 2014)
We present some preliminary empirical results on impact of international certification on export behavior of Russian manufacturing firms. Our research is motivated, first, by the fact that little is known about the impact of ISO certification on the performance of Russian firms and, second, by unclear role of ISO certificate in week local institutional environment (where some firms simply buy these certificates without real audit and modernization of business processes). Russian medium and large enterprises in manufacturing are lagging far behind European peers both in terms of exporting activity and ISO certification level. We are trying to estimate the impact of international certification on the probability of a firm to be involved in foreign trade. We follow the general logic and methodology proposed in papers of Grajek (2004), Clougherty and Grajek (2008), Swann (2010), Otsuki (2011), Martincus et al. (2010), Masacure et al. (2009), Potoski and Prakash (2009). Empirical data comes from two rounds of nation-wide survey on the competitiveness of Russian manufacturing enterprises conducted in 2005 and 2009. We use a panel data from two rounds on approximately 500 firms in eight manufacturing industries. This gives us a unique opportunity to track the history of both availability of ISO certificate and exporting status of the firm. We use several different empirical models to examine the effect of certification on export activity and to control for possible endogeneity by estimating systems of simultaneous equations. We find evidence that ISO certification has a significant positive impact on probability of export if we control for self-selection effect for both export and ISO certification. Firms self-select for ISO by size and productivity as well as by being a supplier of a foreign-owned company in Russia. Then we compared two effects on export performance ? networking with foreign partners and ISO certification. We found out that while there is a direct positive impact of networking with foreign partners and certification on propensity to export, we were unable to find any significant impact of ISO certification on networking with foreign partners as a signal of "common language" that facilitate establishing partnership relations. We conclude that in the period analyzed these two institutions, both being important facilitators of exporting, worked individually.
Keywords: F14; L14; P23; 330; ISO certification; export; manufacturing firms; Russia